EPISTIMOLOGI AR- RAZI DALAM TAFSIR MAFATIH AL GHAIB - Tarto, Tarto (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2023)
Imam Fakhruddin al-Razi, whose capacity and capabilities as a mufassir were still debated even today, has made researchers interested in studying his works. In particular, his commentary entitled Mafatihul Ghaib received much attention and was called a phenomenal work because of its different contents from other commentary books. Mafatihul Ghaib is a book of scientific interpretation that was born from Islamic thought. This is what is interesting for researchers to examine the epistemology of Imam al-Razi's interpretation more deeply. So that researchers can find out how the procedures, or techniques used by Imam al-Razi in producing his commentary. This type of research is completely library research (library research) taking data from the literature that has something to do with the research theme. The analysis technique in this paper uses a content analysis model by exploring and analyzing the interpretation of Imam al-Razi in the book Mafatihul Ghaib